Factors Influencing Resonance Frequency Analysis (RFA) Measurements and 5-Year Survival of Neoss Dental Implants. (1st April 2019) - Andersson, Peter; Pagliani, Luca; Verrocchi, Damiano; Volpe, Stefano; Sahlin, Herman; Sennerby, Lars
Abstract : Background . Diagnostic instruments based on resonance frequency analysis (RFA) can be utilised to assess dental implant stability during treatment and follow-up. Aim . The aim of the present study was to investigate the influence of patient- and implant-related factors on implant stability and the 5-year implant survival. In addition, the influence of stability (ISQ value) at placement and abutment connection on implant survival was evaluated. Materials and Methods . RFA measurements from a total of 334 consecutive patients with 745 dental implants (Neoss Ltd., Harrogate, UK) were retrospectively analysed after at least 5 years in function. Statistics were used to evaluate the influence of the different variables on implant stability and implant survival. Odds ratio calculations were performed to compare the risk for implant failure using 60, 65, 70, and 75 ISQ as threshold levels at placement and loading. Results . A total of 20 implant failures in 14 patients were noted during the 5 years of follow-up, giving an overall cumulative survival rate (CSR) of 97.3% at the implant level and 95.8% at the patient level. Gender, jaw, position, bone quality, and implant diameter had an influence on implant stability at placement. Jaw, bone quality, and implant diameter had an influence on stability after 3-4 months of healing. More failures were observed in full than in partial rehabilitations. Age, gender, jaw, position, bone quantity, bone quality, implant diameter, and implant length had no influence on implant survival. Implants with ISQ values below the threshold levels showed lower survival rates compared to implants with values above these levels. Conclusions . The present study showed a significantly higher risk for implant failure, showing an ISQ value below 70 and 75 at placement or after 3-4 months of healing. The results indicate that RFA measurements can be used to identify implants with increased risk for failure.